2007
DOI: 10.1002/pd.1745
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of tracheo‐oesophageal fistula and oesophageal atresia

Abstract: Of the 32 cases of confirmed TOF/OA,10 (31%) were suspected prenatally. If the TOF/OA was an isolated anomaly (11 cases), the prenatal detection rate was 45%. Interpretation of ultrasound findings suspicious of TOF/OA requires caution, particularly, when there are associated multiple anomalies on scan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 16 publications
0
29
1
1
Order By: Relevance
“…Despite these limitations, one of the strengths of the study is that case identification is likely to be complete because EA is diagnosable either antenatally or at the time of birth and require surgical attention. Recent studies from the Netherlands and Oxford, U.K., reported that diagnosis of EA occurred prenatally in 38% of infants (Choudhry et al, 2007;Garne et al, 2007;de Jong et al, 2010a;Pedersen et al, 2012). Postnatally, EAs are suspected and diagnosed by respiratory or feeding difficulties and inability to pass a nasogastric tube; they are confirmed on chest radiograph with surgical correction within 24 to 48 hours (Spitz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, one of the strengths of the study is that case identification is likely to be complete because EA is diagnosable either antenatally or at the time of birth and require surgical attention. Recent studies from the Netherlands and Oxford, U.K., reported that diagnosis of EA occurred prenatally in 38% of infants (Choudhry et al, 2007;Garne et al, 2007;de Jong et al, 2010a;Pedersen et al, 2012). Postnatally, EAs are suspected and diagnosed by respiratory or feeding difficulties and inability to pass a nasogastric tube; they are confirmed on chest radiograph with surgical correction within 24 to 48 hours (Spitz, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Polyhydramnios is present in approximately 60% of pregnancies with OA/TOF, 29 but polyhydramnios lacks specificity for OA/TOF, as it can be seen in many other conditions and is sometimes an incidental or benign finding. Only about one-third of cases of OA/TOF have both a small or absent fluid-filled stomach and polyhydramnios, 29,30 but the presence of these findings combined is associated with a positive predictive value for OA of 39–56%. 3033 A normal-appearing fluid-filled stomach also occurs in some cases of OA/TOF because the fistula tract between the trachea and lower oesophagus may permit enough fluid passage to fill the stomach.…”
Section: Clinical and Diagnostic Featuresmentioning
confidence: 99%
“…Only about one-third of cases of OA/TOF have both a small or absent fluid-filled stomach and polyhydramnios, 29,30 but the presence of these findings combined is associated with a positive predictive value for OA of 39–56%. 3033 A normal-appearing fluid-filled stomach also occurs in some cases of OA/TOF because the fistula tract between the trachea and lower oesophagus may permit enough fluid passage to fill the stomach. Foetal MRI can be useful when there is suspicion of OA on prenatal ultrasound, and the presence of an upper oesophageal pouch on foetal MRI has a significant positive predictive value for OA/TOF.…”
Section: Clinical and Diagnostic Featuresmentioning
confidence: 99%
“…However, because of the large number of etiologies for these two signs (13,14) and to the subjective nature of a small fetal stomach (12,15,16), EA prenatal diagnosis remains difficult and is characterized both by a high false-positive rate and a poor detection rate. Several studies have documented that the sensitivity of sonography ranges from 8.9 to 42% (6,(17)(18)(19)(20)(21)(22) with Sparey et al (19) reporting a 44% positive predictive value and Stringer et al (22) 56%. Direct visualization of the fluid-filled, blind-ending esophagus during fetal swallowing or upper neck "pouch sign" was described as early as at 23 wk of gestation.…”
mentioning
confidence: 99%
“…Direct visualization of the fluid-filled, blind-ending esophagus during fetal swallowing or upper neck "pouch sign" was described as early as at 23 wk of gestation. However, visualization of the pouch may be challenging owing to technical difficulties or time limitation (20,23,24).…”
mentioning
confidence: 99%